STOMACH CONTENTS OF Galeocerdo cuvieri AND Carcharhinus plumbeus (ELASMOBRANCHII : CARCHARHINIDAE) CAUGHT OFF PARAÍBA STATE, BRAZIL - Shibuya, Akemi; Rosa, Ricardo de Souza; Gadig, Otto Bismarck Fazzano (Arquivos de Ciências do Mar, 2017)
Stomach contents of the sharks Galeocerdo cuvieri and Carcharhinus plumbeus, from Cabedelo county, Paraíba State, Brasil, were analyzed. A total of nine food items were found. The items belonged to six prey groups, including cephalopods, elasmobranchs, and teleosts, all considered common in Northeast Brazil. The stomach contents of G. cuvieri had a stingray of the genus Dasyatis, a skull of Ariidae, three dentitions of Diodon sp., a specimen of Balistes vetula, three nematode parasites and aquatic plant fragments. In the stomach contents of C. plumbeus were found two pairs of beaks of Octopus vulgaris, and dentition and scales of Saparisoma sp. The results obtained in this paper may contribute to the knowledge of the biology of these species on the Brazilian coast.